High jump of impinged droplets before Leidenfrost state - Qiu, Lu (2019)
Unlike the traditionally reported Leidenfrost droplet which only floats on a thin film of vapor, we observe a prominent jump of the impinged droplets in the transition from the contact boiling to the Leidenfrost state. The vapor generation between the droplet and the substrate is vigorous enough to propel the spreading droplet pancake to an anomalous height. The maximum repellent height can be treated as an index of the total transferred energy. Counterintuitively, a stronger vaporization and a higher jump can be generated in the conditions normally considered to be unfavorable to heat transfer, such as a lower substrate temperature, a lower droplet impact velocity, a higher droplet temperature, or a lower thermal conductivity of the deposition on the substrate. Since the total transferred energy is the accumulation of the instantaneous heat flux during the droplet contacting with the substrate, it can be deduced that a longer contact time period is secured in the case of a lower instantaneous heat flux. The inference is supported by our experimental observations. Moreover, the phase diagrams describe the characteristics of the high repellency under different substrate temperatures, droplet subcooling temperatures, and Weber numbers. It allows us to manipulate the droplet jump for the relative applications.